The Role of Physical Activity and Exercise in Cystic Fibrosis – A Literature Review - Anna Bieniasz; Anna Zdziebło; Katarzyna Zdziebło; Maria Sitko; Dominika Stolarczyk; Aleksandra Bąk; Igor Biernacki; Katarzyna Agopsowicz; Katarzyna Blicharz; Martyna Biernacka (Quality in Sport)
Cystic fibrosis (CF) is one of the most widespread genetic disorders worldwide. The disease is caused by a mutation in the CFTR gene, which impairs the transport of chloride and bicarbonate ions across the cell membrane, leading to dysfunction of multiple organ systems - primarily the respiratory and digestive systems. Over the years, the availability of new pharmacological therapies has significantly improved both the quality and length of life in CF patients. Nevertheless, non-pharmacological treatment remains an integral component of the overall therapeutic approach. Physical activity is recommended not only for the general population but is also increasingly recognized for its beneficial effects in patients with various chronic diseases. The multifaceted impact of exercise on the human body is a frequent subject of scientific investigation. With the increasing life expectancy of individuals with CF, there is a growing risk of developing comorbidities, including lifestyle-related diseases, which may lead to overlapping symptoms. In modern clinical practice, cystic fibrosis is not always the direct cause of death in these patients. Therefore, it is crucial to adopt a holistic approach to the health of CF patients. Numerous studies have investigated the role of physical activity and exercise in cystic fibrosis, highlighting both the benefits and limitations imposed by the disease. Positive outcomes have been reported, including improved physical performance parameters, which contribute to enhanced quality of life and overall functioning. Additionally, exercise has been associated with improved mental health. A key conclusion emerging from these studies is the importance of personalized treatment plans that consider disease severity, physical and economic conditions, and the need to support patient motivation and adherence to exercise regimens.